“In the centre and in the regions”. Features of the campaign to confiscate Church valuables, and the organisation of a schism in Turkestan diocese (1922–1923) - Ekaterina Ozmitel (Vestnik Pravoslavnogo Svâto-Tihonovskogo Gumanitarnogo Universiteta: Seriâ II. Istoriâ, Istoriâ Russkoj Pravoslavnoj Cerkvi)
The article highlights the first period of the Soviet government's systematic struggle with the Russian Orthodox Church using the example of the Turkestan and Tashkent dioceses. It was an organized, tightly centralized campaign that began under the pretext of the need to withdraw all church valuables to help the hungry. The real goal of the campaign was to solve the financial problems of the Soviet state by defeating the Church (confiscation of valuables and organization of the Renovationist schism). In 1922, there were extremely few valuable items in the churches of the Turkestan ASSR, nevertheless, in the summer, with a delay of several months, the expropriation of church values was carried out here. The details of the withdrawal procedure are shown on the example of the churches of Alma-Ata, Tashkent and rural temples. The second goal of the withdrawal campaign – the elimination of the canonical system of church administration and its replacement with renovationist structures – in the Turkestan diocese was achieved by mid-1923. The specifics of achieving this goal were clarified by comparing the local church chronicle with the central plan of the campaign. Thanks to this, it became possible for the first time to explain the logic of the events that took place in the Tashkent in late 1922 – early 1923, and to explain the reasons for the sudden refusal of Archbishop Innokenty (Pustynsky) from the administration of the Turkestan diocese and his departure from Tashkent.